Turnover factors of auditors in big six and non-big six firms - Sim, Mui Gek (2015)
This research presents the findings of a survey which looked at the impact of the factors influencing intended turnover of auditors, as well as the differences in responses between a Big 6 auditor and a non-Big 6 auditor. The questionnaire, which was sent in August 1993 to 240 auditors in both Big 6 and non-Big 6 firms, had a response rate of 39% and 68% for the Big 6 and non-Big 6 auditors respectively. Results of the study showed that there are indeed different factors affecting staff turnover for Big 6 and non-Big 6 firms. For the Big 6 auditors, they were primarily dissatisfied with the amount of overtime they had to do. They were also not happy with the effect of the overtime work on their social lives. For the non-Big 6 auditors, they were generally not satisfied with their promotion opportunities and working environment. They were also more inclined to think of leaving the firm when they are frustrated with their work. Apart from these differences, both groups of auditors generally agree that auditing does have its 'plus' points in that they have friendly auditees, audit is not boring, and the rules and regulations are satisfactory.